Asosiasi Baru New association between Cecidochares connexa (M.) (Diptera: Tephritidae) and local parasitoids: Revisiting classical biological controlantara Cecidochares connexa (M) (Diptera: Tephritidae) dengan Parasitoid Lokal: Sebuah Tinjauan Terhadap Pengendalian Hayati Klasik : Asosiasi baru antara Cecidochares connexa (M) (Diptera: Tephritidae) dan parasitoid lokal: Sebuah tinjauan terhadap pengendalian hayati klasik - Harianto, Muhammad; Triwidodo, Hermanu; Agus, Nurariaty; Buchori, Damayanti (Perhimpunan Entomologi Indonesia, 2024)
The gall fly Cecidochares connexa (L.) (Diptera: Tephritidae) was introduced in Bantimurung, Polewali Mandar Regency, South Sulawesi in 1999, to control the Siam weed Chromolaena odorata, an invasive weed from Florida, United States. However, some previous studies have shown that C. connexa can be attacked by local predators and parasitoids, which can affect the effectiveness of C. connexa in the field. The objective of the research is to study the new interaction and association between the introduced C. connexa, and local parasitoids. The research was conducted in April-December 2021 at two habitats namely open fields and cocoa plantations, in four villages of Polewali Mandar Regency. Purposive sampling was conducted to collect C. odorata infested by the gall flies. Thirty C. odorata samples were collected from three different sites at each habitat and each village. The galls were grouped into two different categories i.e. those with and with out holes. The galls with holes were then reared until the insects emerged and the insect specimens were identified. The research results showed that the gall numbers, healthy and parasitized C. connexa at opened areas were significantly higher as compared to cocoa plantations. Parasitism phenomenon indicated the new interaction and association between the C. connexa with the local parasitoids. The parasitization rate of C. connexa in the opened fields (23.24%) was not significantly with in the cocoa plantations (28.84%). On the parasitized C. connexa were found four families of parasitoids i.e. Eulophidae, Braconidae, Eupelmidae, and Ormyridae. The dominant parasitoid found was Quadrastichus sp.1, with the parasitization rate of 14% in open fields and 10% in cocoa plantations.